Does family mealtime have a protective effect on obesity and good eating habits in young people? A 2000-2016 review - Abykeyla Mellisse Tosatti; Letícia W. Ribeiro; Rachel Helena Vieira Machado; Priscila Maximino; Ana Beatriz Bozzini; Cláudia de Cássia Ramos; Mauro Fisberg
Abstract Objectives: to review the prevalence of family meals and its impact on BMI and eating habits during childhood and adolescence. Methods: reviews are from Bireme / Lilacs / Scielo / Cochrane and Pubmed, between 2000-2016 with descriptors "family meal or mealtime", "behavior", "nutrition or diet or consumption or eating", and "child or children or adolescence"; performed by two independent examiners, according to the systematic steps in English and Portuguese. The articles were selected based on prevalence and/ or discussion between nutritional variables. 2,319 articles were found, which 15 were selected all in English: systematic reviews (n=2), cross-sectional studies (n=8), longitudinal studies (n=8); all related to children (n=5), adolescents (n=6) and both (n=5). Results: the mean of shared meals was 1x/day, with a prevalence of 27 to 81%. Most studies (n=13) reported the beneficial impact on BMI, higher consumption of fruit and vegetables, protein, calcium and a lower consumption of sweets and sugar sweetened beverages, family union and self-regulation of appetite. Conclusions: having daily family mealtime has beneficial effect on the nutritional status and children and adolescents' eating behavior.